Chemical Vapor Deposition of Phase‐Pure Uranium Dioxide Thin Films from Uranium(IV) Amidate Precursors. (20th March 2019) - Straub, Mark D.; Leduc, Jennifer; Frank, Michael; Raauf, Aida; Lohrey, Trevor D.; Minasian, Stefan G.; Mathur, Sanjay; Arnold, John
Abstract: Homoleptic uranium(IV) amidate complexes have been synthesized and applied as single‐source molecular precursors for the chemical vapor deposition of UO2 thin films. These precursors decompose by alkene elimination to give highly crystalline phase‐pure UO2 films with an unusual branched heterostructure.